The diving bell and the butterfly : a memoir of life in death - Bauby, Jean-Dominique, 1952-1997 (Vintage Books, 1998)
In 1995, Jean-Dominique Bauby was the editor in chief of French Elle, the father of two young children, a forty-three-year-old man known and loved for his wit, his style, and his impassioned approach to life. By the end of the year he was also the victim of a rare kind of stroke to the brain stem. After twenty days in a coma, Bauby awoke into a body that had all but stopped working: only his left eye functioned, allowing him to see and, by blinking, to make clear that his mind was unimpaired. Almost miraculously, he was soon able to express himself in the richest detail, blinking to select letters one by one as a special alphabet was slowly recited to him, over and over again. In the same way, he was eventually able to compose this extraordinary book. By turns wistful, mischievous, angry and witty, Bauby bears witness to his determination to live as fully in his mind as he had been able to in his body. He explains the joy, and the deep sadness, of seeing his children and of hearing his aged father's voice on the phone. In magical sequences, he imagines traveling to other places and times; of lying next to the woman he loves. Fed only intravenously, he imagines preparing and tasting the full flavor of delectable dishes. Again and again he returns to an "inexhaustible reservoir of sensations," keeping in touch with himself and the life around him.